Advanced Processing of 2D Marine Reflection Seismic Data Using the Common Reflection Surface (CRS) Stack Method with K-L Filter Application: Pengolahan Lanjut Data Seismik Refleksi 2D Lait Menggunakan Metode Common Reflection Surface (CRS) Stack dengan Penerapan KL-Filter - Emir Dzakwan Kamal Zein; Syamsurijal Rasimeng; Egie Wijaksono (JURNAL GEOCELEBES, 2023)
Data processing using the seismic reflection method is an important stage in the exploration of natural resources and minerals. This research was conducted to determine the effective and efficient stacking and filtering methods in reconstructing the subsurface geological structure of the earth from the results of data processing using ProMAX software. The data processing method used is the conventional stack and the Common Reflection Surface (CRS) stack. Aperture values of 0 ms – 50 m and 3000 ms – 150 m in the CRS stack process produce the most optimum seismic sections. Both methods produce a different quality of seismic cross-section display. The 2D cross-section model from the conventional stack method looks noisier than the results from the CRS stack method. In addition, the reflector pattern on the cross-section of the results of the CRS stack method is clearer and visible with a relatively large amplitude compared to the results of the conventional stack method. To maximize the quality of data display, data enhancement is applied, which is the K-L filter. The eigenimages value of 0.10% on the K-L filter with a horizontal window width of 120 is used to reduce random noise. Thus, an increase in the S/N ratio will be obtained in the seismic data so that the 2D cross-sectional model of the seismic reflection method can approach the original conditions of the subsurface geological structure.